Development Of Technological Schemes For Transporting Rock Mass And Management Of The Working Area Of A Deep Quarry (Texas Journal of Engineering and Technology, 2025)
The operating conditions of modern industrial vehicles are determined by the increasing depth of mining operations. This trend results in the predominant use of vehicles (over 60%) as assembly units, concentrating vehicle traffic in the working area of deep quarries with their limited space of the Muruntau deep quarry is characterized by a high concentration of traffic, heterogeneity of the transported rock mass, and instability of key parameters. During a shift, 10-15 working faces and 5-10 transfer points are in operation, forming over 100 routes with an average length of 3.73 km. The maximum freight traffic intensity on individual routes reaches over 35,000 m³ of rock mass per shift. The share of face roads along the traffic routes is 15-30%. Up to 80% of the roads have a service life of up to one year. The complexity of operating conditions is exacerbated by the high concentration of mining equipment and minimal excavation space.